Peripheral T-Cell Lymphoma with Aberrant Expression of CD19, CD20, and CD79a: Case Report and Literature Review - Rahul G. Matnani; Rachel L. Stewart; Joseph Pulliam; Chester D. Jennings; Melissa Kesler (Case Reports in Hematology)
A case of lymphoma of T-cell derivation with aberrant expression of three B-cell lineage markers (CD19, CD20, and CD79a), which was diagnosed on a left axillary excision, is described. Immunohistochemical studies and flow cytometry analysis demonstrated neoplastic cells expressing CD3, CD19, CD20, and CD79a with absence of CD4, CD8, CD10, CD30, CD34, CD56, CD68, TDT, MPO, PAX-5, and surface immunoglobulin. Gene rearrangement studies performed on paraffin blocks demonstrated monoclonal T-cell receptor gamma chain rearrangement with no evidence of clonal heavy chain rearrangement. The neoplastic cells were negative for Epstein-Barr virus (EBV) or Human Herpes Virus 8 (HHV-8). At the time of diagnosis, the PET scan demonstrated hypermetabolic neoplastic cells involving the left axilla, bilateral internal jugular areas, mediastinum, right hilum, bilateral lungs, and spleen. However, bone marrow biopsy performed for hemolytic anemia revealed normocellular bone marrow with trilineage maturation. The patient had no evidence of immunodeficiency or infection with EBV or HHV-8. This is the first reported case of a mature T-cell lymphoma with aberrant expression of three B-cell lineage markers. The current report also highlights the need for molecular gene rearrangement studies to determine the precise lineage of ambiguous neoplastic clones.